Az egészségturisztikai fejlesztések hatásai különös tekintettel Kelet-Magyarországra - Molnár, Csilla (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
In Eastern Hungary in recent years, there have been many developments in health tour-ism - including spas - for which the effects have not yet fully materialised. It is not possi-ble, for reasons of length, to provide a detailed, critical analysis of each project. Therefore the study of flagship projects is used to provide overall analysis of the direct and indirect impact of investment activities